Kompetensi Pedagogik Guru dalam Implementasi Pembelajaran Tematik Terpadu di Madrasah Ibtidaiyah - Tutuk Ningsih; Mursida Aziz; Sutrimah Sutrimah; Nur Listianingsih; Azkia Khoerul Elfinda (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2021)
One of the competencies of teachers in the 21st century is pedagogical competence. This competence is one of the important factors in determining the success of teachers in carrying out teaching and learning activities. This study aims to analyze the pedagogical competence of teachers in integrated thematic education at Madrasah Ibtidaiyah Ma'arif 04 Gentasari. This research is field research using a qualitative approach. Data collection uses three techniques, namely: field observation, direct interviews with informants, and documentation. After the data is collected, the data is analyzed by reducing, presenting, and verifying the data. The result of this research is that the teacher has met the standard of pedagogic competence. This is indicated by the understanding and analysis that educators get from students. The fulfillment of the standard of teacher pedagogical competence is evidence of the achievement of educators in providing for the needs of students. Educators' pedagogical competences include implementing learning, planning and conducting learning assessments, analyzing the findings of the evaluation to identify the level of learning mastery, and using the results to improve the quality of learning programs. The development carried out in learning at MI Ma'arif 04 Gentasari has a good system. In addition, it is also supported by competent educators to provide well-established teaching to students.